Modeling Near Field Air Pollution In USM : Effects Of Downwash. - Teh, Su Yean; Koh, Hock Lye; Md Ismail, Ahmad Izani (2004)
Several research projects are currently undertaken to pursue the goals stipulated in the Healty Campus Program in USM. One Of the main concern is the air pollution coming from the School Of Chemical Sciences and its potential impact on the health of occupants in the surrounding buildings. A previous study has concluded that the potential negative health impact is negligible. The previous study however has ignored the effects of nearby buildings on the dispersion of air plumes. When the distance between the stack and the target building is short , the target building will produce wake effects that may in turn cause an increase in the concentrations of plumes behind the building. Hence the ability to simulate the effects of downwash due to the target buildings is desirable in order to provide a better estimation of the pollutant concentrations near the target buildings. Meteorology parameters such as wind conditions atmospheric stability play an important role in the distribution of th plumes. This paper will present a model analysis of air pollution including the effects of the downwash due to near buildings by using the ISC-AERMOD View models. Some result from the study will be presented to indicate that the air pollution levels will not pose a health hazard to the occupants despite the downwash.